(untitled) (Spectrum of Humanities and Social Sciences, 2025)
This study aims to analyze the socioeconomic transformation of the Indigenous Raji community in the Surkhet District focusng on changes in gender roles, cultural identity, livelihoods, education, and health. In order to achieve the objective, the study combined exploratory and descriptive methods in a mixed-methods design. In Thauri Village, Surkhet all 11 Raji households took part in a comprehensive household census, which provided the study with both qualitative and quantitative data. Among the methods used to gather the data were structured questionnaires, key informant interviews, and field observations. According to the findings, there has been a notable shift from a traditional, forest-dependent way of life to a more settled and diversified economy that includes small businesses, wage labor, salaried jobs, and migration, mostly to India. Although problems like school dropouts, under-representation in decision-making, and the loss of traditional culture, language, and attire persist, there has been progress in the areas of education, healthcare, sanitation, and women’s participation. All 11 Raji households, with a literacy rate of 35.06 percent, are still below the poverty line, according to a census. The necessity for culturally sensitive development is highlighted by the fact that 72.72 percent of respondents still rely on wells or streams for water, even though all of them use contemporary medical care. The study concludes that in order to support sustainable development, particular policy interventions are needed to reduce poverty, improve the standard of living for Raji people, and protect their declining indigenous language, culture, and knowledge.